INFON-A Unit for Information Measurement in an Organised System as an Approach to Measure Technical Information of a Document - Gowtham, M. S. (Journal of Information and Knowledge, 1995)
A concept of measuring the quantity of information in an organised system is introduced. Unit of information and conditions of an organised information system are defined. A term INFON is coined to denote the unit of information. It is suggested to extend the concept of organised information system to a technical document to measure the quantity of technical information in a document.